2022
DOI: 10.1002/anie.202202232
|View full text |Cite
|
Sign up to set email alerts
|

Modular Nitrogen‐Doped Concave Polycyclic Aromatic Hydrocarbons for High‐Performance Organic Light‐Emitting Diodes with Tunable Emission Mechanisms**

Abstract: Although bowl‐shaped N‐pyrrolic polycyclic aromatic hydrocarbons (PAHs) can achieve excellent electron‐donating ability, their application for optoelectronics is hampered by typically low photoluminescence quantum yields (PLQYs). To address this issue, we report the synthesis and characterization of a series of curved and fully conjugated nitrogen‐doped PAHs. Through structural modifications to the electron‐accepting moiety, we are able to switch the mechanism of luminescence between thermally activated delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 50 publications
1
51
1
Order By: Relevance
“…1–8 The most widely used strategy is the doping of boron (B) and nitrogen (N) atoms into the PAHs because B and N atoms can exert complementary electron-accepting and electron-donating properties, respectively, on the π-conjugated framework, allowing the modulation of the HOMO and LUMO distributions and their energy gap. 9–18 Among B,N-doped PAHs, the derivatives of B , N -diphenyl-5,10-dihydro-dibenzo-1,4-azaborine, namely, dibenzoazaborine, 19,20 have recently attracted significant attention because the dibenzoazaborine skeleton may constitute the main component of highly efficient emitting materials such as thermally activated delayed fluorescence (TADF) compounds. 21,22 More interestingly, B,N-doped PAHs containing multiple azaborine rings have exhibited excellent photophysical properties such as narrowband emissions with high photoluminescence quantum yields (PLQYs) due to the multi-resonance effects of B and N atoms that confine the HOMO and LUMO on different ring atoms.…”
Section: Introductionmentioning
confidence: 99%
“…1–8 The most widely used strategy is the doping of boron (B) and nitrogen (N) atoms into the PAHs because B and N atoms can exert complementary electron-accepting and electron-donating properties, respectively, on the π-conjugated framework, allowing the modulation of the HOMO and LUMO distributions and their energy gap. 9–18 Among B,N-doped PAHs, the derivatives of B , N -diphenyl-5,10-dihydro-dibenzo-1,4-azaborine, namely, dibenzoazaborine, 19,20 have recently attracted significant attention because the dibenzoazaborine skeleton may constitute the main component of highly efficient emitting materials such as thermally activated delayed fluorescence (TADF) compounds. 21,22 More interestingly, B,N-doped PAHs containing multiple azaborine rings have exhibited excellent photophysical properties such as narrowband emissions with high photoluminescence quantum yields (PLQYs) due to the multi-resonance effects of B and N atoms that confine the HOMO and LUMO on different ring atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Wagner et al reported one of such systems, which realized the maximum external quantum efficiency of 12% for OLED devices. 41 The strategy they adopted for HOMO−LUMO separation is inserting an antiaromatic seven-membered ring between the D and A groups. Further development of rational molecular design strategies is still of the highest priority in the development of D−A-type fused-ring TADF systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a result, D–A-type fused-ring TADF systems are very rare. Very recently, Wagner et al reported one of such systems, which realized the maximum external quantum efficiency of 12% for OLED devices . The strategy they adopted for HOMO–LUMO separation is inserting an antiaromatic seven-membered ring between the D and A groups.…”
Section: Introductionmentioning
confidence: 99%
“…The singlet–triplet energy splitting between the S 1 and T 1 states (Δ E ST ) and spin–orbit coupling (SOC) play key roles in manifesting the TADF character of an organic compound. To boost the rISC process, ideally, the Δ E ST is zero or even negative [ 12 13 ], while the SOC is as large as possible. One of the promising molecular design strategies to meet the above-mentioned criteria involves a highly twisted (D) n –(A) m (D: electron donor; A: electron acceptor) system, in which efficient intramolecular charge transfer (ICT) occurs in the singlet excited state ( 1 CT).…”
Section: Introductionmentioning
confidence: 99%